Pembuatan Silika High Grade Dari Fly Ash Sawit Dengan Proses Ekstraksi Dan Cation Exchange - Ahmad Zaki; Edy Saputra; Ahmad Fadli (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
One alternative raw materials manufacture of high grade silica is using palm oil mill fly ash. This research aimed to study the effect of temperatureprocess, time and the ratio mass of zeolite and obtain optimum conditions cation exchange process (Fe) in a solution of sodium silicate with raw material palm oil mill fly ash. Palm oil mill fly ash is heated using oven at 105° C for 24 hours. Then fly ash reacted with 1,4N NaOH solution at 105° C for 50 minutes. Then obtained sodium silicate solution is reacted with Na-zeolite. The results of the optimization then precipitated using 10% H2SO4 and derived solidsilica. XRF analysis results showed solid silica has a purity of 96.129%.Keyword:Precipitation, Zeolite